The effect of temperature reduction on the performance and stability of UASB reactors treating synthetic sewage - Masood Abdusalam Ghanem Ali (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
The objective of this investigation is to determine the effect of temperature reduction on the performance and stability of laboratory-scale up-flow anaerobic sludge blanket (UASB) treating synthetic sewage. The work was carried out using four 4-litre continuously fed UASB reactors. The operation started at a constant hydraulic retention time of 24 hours (up flow velocity 0.02 m hour-1) and an influent COD concentration of 2250 mg l-1, with an organic loading rate of 2.25 g COD l-1 day-1. During the experiment, the operating temperature was reduced in a single step from 35 to 30 ⁰C, then stepped down to 25 ⁰C. COD removal efficiency fell slightly from 96 % in all reactors to 93%. Effluent TSS concentrations remained below 20 mg l-1 and TSS removal efficiency ranged between 93-98%. Gas production showed a slight disturbance following the initial drop in temperature to 30 ⁰C, but stabilised at around 0.74 l CH4 l-1, 0.30 l CH4 g-1 COD added and 0.31 l CH4 g-1 COD removed. The subsequent drop to 25 ⁰C produced a stronger disturbance, but both volumetric and specific methane production recovered to the previous values by about day 412. The average biogas methane content in all reactors was unchanged or marginally higher at 78-79%.